Process optimization of spray-dried whole porcine blood powder using response surface methodology central composite design (RSM-CCD) - Sapuay, Arlyn Gail M.; Rustia, Abigail S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2021)
Underutilization of porcine blood implied loss of a good source of proteins high in nutritional content and functional quality, economic losses, and potential environmental hazard. As a response, this study aimed to optimize the spray-drying parameters (Inlet Temperature, ℃; and Pressure, psi) of whole porcine blood powder using the Central Composite Design of Response Surface Methodology (RSM) through the evaluation of the effects on moisture content, water activity, bulk density, solubility, color (CIE L*a*b* values), and yield. It also aimed to establish optimum process parameters maximizing the yield, while minimizing the moisture content, water activity, and bulk density of the resulting product using mathematical models. Data analysis using ANOVA and lack-of-fit tests showed the significance (p<0.05) at 95% confidence level) of the models generated for moisture content, water activity, color (CIE a* value), and bulk density, which also had the highest adjusted R2 value (0.981). The adequacy of these statistical models to generate sound predictive models was then validated. The experimental values obtained from the optimal solution were noted to be within the confidence (CI, 95%) and prediction (PI, 95%) intervals, satisfying the predicted model.
The whole porcine blood powder processed under the optimal spray-drying parameters (200℃; 400 psi) was characterized to obtain bulk (0.305 g/cm3) and tapped (0.365 g/cm3) density values within the literature range; with “very good” flowability (Carr’s Index=16.374), and “low” cohesiveness (Hausner Ratio=1.196). The reconstituted form, on the other hand, was observed to be dull and low in color intensity due to its “weak” saturation index value (Chroma=1.297), and have pH value (7.473) within the literature range (pH 6.7-7.5).
Thesis ( B.achelor of Science in Food Technology)--University of the Philippines Diliman
Bibliography : pages 56-67.
Keywords: Cooking (Blood).; Swine -- Philippines; Spray drying; Slaughtering and slaughter-houses -- By-products -- Philippines